Experimental mesenteric ischemia. Radioisotopic diagnosis - Alberti, Carlos; Dallaglio, Juan J; Sarra, Luis D; Obiols, Eugenio F; Rodríguez Santos, Emilio; Delgado, Eduardo; Castelleti, Luis (Cirugía del Uruguay, 1995)
A noninvasive radionuclide technique with 99-Tc-DMP far the early diagnosis of sma/1 bowel infarction due to mesenteric artery compression, was evaluated. T he usefullness of 99-Tc-DMP and /he critica/ preassure of mesenteric artery were demostrated. The diagnosis was performed befare one hour had past from the begining of the ischemia.